MEMBANGUN KELUAGA QUR’ANI DI ERA DIGITAL, ANTARA HARAPAN DAN TANTANGAN - Fajarwati, Fajarwati (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2023)
The Qur'anic family is a family that is close to the Qur'an, friendly to the Qur'an, always interacts with the Qur'an, and practices the Qur'an in everyday life. The Qur'ani family is not just a family that memorizes the text of the Qur'an, but is also able to practice Qur'anic values ​​in its family life. The Qur'an is a guide and reference in forming a real family. The Qur'an cites various family models as a reflection of today's modern family. For example, the bad family model reflects the Abu Lahab family (Qs. Al-Lahab: 1-5), the noble family reflects the family of Prophet Ibrahim (Qs. Ash-Shaffat: 101-113), Imran's family (Qs. Ali Imran: 33-34 ), the Luqman family (Qs. Luqman: 13-19) and so on. These are among the family stories (al-Qashash) that are revealed in the Qur'an as a reflection of today's family. Therefore, it is appropriate for every family to reflect on the various family models described in the Qur'an so that they can build a Qur'anic family